Transient Fetal Tachycardia After Intravenous Diphenhydramine Administration. Issue 2 (August 2017) - Abernathy, Alice; Alsina, Laura; Greer, Jessica; Egerman, Robert
Abstract : BACKGROUND: Fetal tachycardia is attributable to a variety of etiologies, including an untreated maternal medical condition or an indicator of potential fetal compromise. Maternal medication administration may also affect the fetal heart rate. CASE: A 28-year-old nulliparous patient at 41 weeks of gestation was treated for pruritus with intravenous diphenhydramine after epidural administration of fentanyl. Within 14 minutes, the fetal heart rate increased from a baseline of 155 beats per minute (bpm) to more than 200 bpm while maintaining moderate variability. This was accompanied by an increase in uterine contractions occurring every 1.5 minutes. The fetal tachycardia lasted 51 minutes; several hours later, a healthy neonate was delivered. CONCLUSION: Diphenhydramine may produce transient fetal tachycardia as well as increased maternal uterine activity. Abstract : Intrapartum maternal administration of diphenhydramine may result in transient fetal tachycardia as well as increased uterine activity.